Differential Recruitment of Medial and Lateral Gastrocnemius During Heel Raises: Role of Ankle ROM, Unilateral Execution, and Limb Dominance - Ana María Ferri-Caruana; Alvaro Juesas; Angel Saez-Berlanga; Juan C. Colado (Applied Sciences)
Background: The medial (MG) and lateral gastrocnemius (LG) muscles exhibit differential activation patterns during plantar flexion tasks. However, the influence of range of motion (ROM), exercise type (unilateral vs. bilateral), and limb dominance on muscle activity during heel raise exercises (HREs) remains unclear. Methods: Nineteen physically active adults performed unilateral and bilateral HREs under two ankle ROM conditions: neutral (NROM) and full (FROM). Surface electromyography (EMG) was collected from both legs during each condition and normalized to peak values recorded during overground sprinting. Results: MG activity was significantly higher during the FROM than the NROM, in both the dominant leg (F = 11.55, p < 0.01, η2 = 0.47) and the non-dominant leg (F = 6.63, p < 0.05, η2 = 0.31), and was not affected by exercise type. In contrast, LG activity increased significantly during unilateral versus bilateral HREs, especially in the dominant leg during the FROM (F = 17.47, p < 0.01, η2 = 0.52) and in the non-dominant leg (F = 5.44, p < 0.05, η2 = 0.25). Activation ratios (MG:LG) differed significantly between dominant and non-dominant legs only in the unilateral FROM (p = 0.03). MG activation during the unilateral FROM was comparable to sprinting values, highlighting its high neuromuscular demand. Conclusion: The MG and LG respond differently to exercise parameters. The MG is primarily influenced by ROM, whereas the LG is sensitive to both exercise type and limb dominance. These findings emphasize the importance of ROM manipulation and unilateral training to target specific gastrocnemius regions. FROM and unilateral execution optimize gastrocnemius activation, with implications for rehabilitation and performance programs targeting calf musculature.